1998
DOI: 10.1002/(sici)1099-0690(199811)1998:11<2425::aid-ejoc2425>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectronic Inhibition of Deprotonation in the Radical Cation ofN-Benzylpiperidine: a Contribution to the Debate on the Mechanism ofN-Dealkylation of Tertiary Amines

Abstract: Evidence for a stereoelectronic inhibition of deprotonation of the radical cation of N‐benzylpiperidine is presented. This stereoelectronic effect, which is due to the cyclic structure of the precursor, provides a tool to differentiate hydrogen‐atom‐ versus electron‐transfer routes in the biomimetic oxidative N‐dealkylation of tertiary amines: the electron‐transfer route appears to be the operating mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…At the same time, on keeping constant the pH value, a linear dependence of k exp with the amine concentration was observed. It follows that the ET-reaction is first-order in both [4A] and [1], as expected. 7a,8 As no significant differences were observed between the k exp values determined in this way (with extraction; ~ 3 half-lives) and those obtained directly on the somewhat cloudy reaction mixture (no extraction; ~ 1 half-live), the more easy direct method was adopted to determine k exp at other pH values.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…At the same time, on keeping constant the pH value, a linear dependence of k exp with the amine concentration was observed. It follows that the ET-reaction is first-order in both [4A] and [1], as expected. 7a,8 As no significant differences were observed between the k exp values determined in this way (with extraction; ~ 3 half-lives) and those obtained directly on the somewhat cloudy reaction mixture (no extraction; ~ 1 half-live), the more easy direct method was adopted to determine k exp at other pH values.…”
Section: Methodssupporting
confidence: 82%
“…Starting from [1] 0 = 0.03 M, the same concentration of the kinetic experiments to be reported below, a detailed search revealed that [1] ] 0 ratio was twice the generally accepted 16 stoicheiometric value (i.e., 1:2). On the other hand, blank and oxidation experiments showed both the HETERO and ET rates decreasing with increasing pH value.…”
Section: Methodsmentioning
confidence: 99%
“…The UV spectrum is similar to that of CpQ; therefore, the modification in the molecule should be away from the chromophores. The chemistry of amine oxidation is well-known, and it is widely accepted to occur by either hydrogen atom transfer (HAT) or single-electron transfer (SET) mechanisms. Secondary amines oxidize to hydroxylamine that leads to loss of water and are further oxidized to nitrone [CpQ-nitrone (Scheme )].…”
Section: Resultsmentioning
confidence: 99%
“…Several possibilities might be advanced for the formation of iminium cations, but we cite only three: (i) hydrogen-atom-transfer (HAT), (ii) electron-transfer (ET), or, by analogy with the RuO 4 -oxidation of esters, 11 (iii) a concerted mechanism with an S E 2-like transition state. We discovered previously 12 that 1B undergoes oxidation to 8B and 11 in bona fide HAT or ET conditions with regioselectivities (alkyl/benzyl) of 0.7 and 0.4, respectively. These values are significantly different from that of 2.1 found for 1B in the present paper.…”
Section: A-bmentioning
confidence: 96%